The Increase Capabilies Knowledge Of Science With A Experiment In 5-6 Years Old At Immanuel Kidergarten. - Oktaria Lukas; Evie Palenewen; Fachrul Rozie (Universitas muhammadiyah Banjarmasin, 2024)
The goal to be achieved in this study is to determine the increase capabilies knowledge of science with a experiment in 5-6 years old at Immanuel Kidergarten. The type of research used is a Classroom Action Research (CAR) with planning, implementation, observation, and reflection. Subject and object of this research were the group B of Immanuel Kidergarten, which consisted of 22 childern, consist 13 girls and 9 boys. The research consisted of 3 cycle which one every cycle had 3 meets. Data collection techniques were interviews, observation, documentation. The data obained from this study were is form of simple experiment ability vlues for each child and were then analyzed with siple statistics to obtain an average value. The result showed that use of experiment science with mixed coloring could improve that abilities children in group B Immanuel Kidergarten. The increase capabilities of the first cycle showed increase had increase was gratifying result, this increaseus evident from the first cycle of 46% (Develop) this cycle due child has hesistant and afraid do experiment. The increase capabilities of the second cycle showed increase science had increase was gratifying result, this increases evident from the second cycle of 69,4% (Very Good) this cycle half of children been brave for experiment and half children can’t focus because they having play on they self, the increase capabilities of the last cycle showed increase science had increase very well, thus uncreases evident from the last cyle of 84% (very Well) the last cycle due teacher and research giving much example experiment so children love this studies. And have achieved the criteria set by the completeness score of the increase capabilities knowledge of science with a experiment in 5-6 years old at Immanuel Kidergarten Samarinda.